Causes of delayed first medical contact (FMC) to balloon time in patients undergoing primary percutaneous coronary intervention (PCI) - Siddiqui, Muhammad Azeem Abdullah; Irshad, Yasir; Khalid, Muhammad Sarwar; Zafar, Qudsia; Nasir, Zeshan; Nazar, Mubashar (Biological and Clinical Sciences Research Journal, 2025)
Timely primary percutaneous coronary intervention (PCI) is critical in managing ST-segment elevation myocardial infarction (STEMI), with door-to-balloon (D2B) time being a key quality-of-care metric. Delays in first medical contact (FMC) to balloon time are associated with increased mortality, especially in low-resource settings like Pakistan. Objective: To identify and quantify the causes contributing to delayed FMC-to-balloon time in STEMI patients undergoing primary PCI at a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted at the Cardiac Complex of Bahawal Victoria Hospital, Bahawalpur, from October 2024 to March 2025. A total of 142 patients aged 18–65 years with confirmed STEMI undergoing primary PCI were recruited using non-probability consecutive sampling. Causes of delay beyond 90 minutes from FMC to balloon inflation were assessed, including consent-related issues, physician misinterpretation, procedural delays, diagnostic delays, catheterization lab readiness, and inter-facility referrals. Data were analyzed using SPSS v25.0 with descriptive statistics and chi-square tests for stratified analyses. Results: The mean age of participants was 52.2 ± 6.7 years, with 69.0% males. Most patients were from rural areas (58.5%) and had low educational attainment. The most common cause of delay was delay in obtaining consent or attendant availability (59.9%), followed by physician misinterpretation at FMC (38.7%). Procedure-related, diagnosis-related, cath lab readiness, and referral-related delays were observed in 9.9% to 14.1% of cases. Female patients experienced significantly more consent-related delays (65.9% vs. 57.1%), and misinterpretation was more common among rural patients (40.0% vs. 37.3%). Conclusion: Delays in FMC-to-balloon time in STEMI care are predominantly caused by consent-related barriers and diagnostic misinterpretation at first contact, especially in rural and female patients. Targeted interventions such as pre-hospital education, streamlined consent protocols, physician training, and improved emergency infrastructure are essential to reduce D2B times and improve clinical outcomes.